Reduced tracheal stenosing effect of nintedanib in a patient with scarred posttraumatic tracheal stenosis and airflow limitation - a case report - Stefanie Klampfleitner; Andreas Fertl; Ositha Prinz; Martin Doerfler-Schalm; Dieter Munker; Markus O. Henke (Respiratory Medicine Case Reports)
Introduction: Nintedanib is a tyrosine kinase inhibitor and has been approved for the treatment of idiopathic pulmonary fibrosis (IPF) since 2020. In Clinical trials, the antifibrotic effect of nintedanib was shown. Case: A 60-year-old female medical assistant, infected with COVID-19 in 10/2020, experienced a complicated course of disease leading to tracheal stenosis. Various interventions, including stent placements and tracheal surgeries, were performed. Due to recurrent restenosis, the patient was treated with nintedanib, a tyrosine kinase inhibitor used in idiopathic pulmonary fibrosis. The treatment spanned 306 days, during which the patient showed stability in pulmonary function. Nintedanib demonstrated a potential anti-inflammatory effect, reducing the frequency of interventions and prolonging stent-free intervals. The results suggest possible efficacy of nintedanib in managing scar-related granulation tissue, highlighting its potential in treating tracheal stenosis. Conclusion: This case shows a decreased need for interventions, and the longer duration of stent placement may suggest a potential role for nintedanib in diminishing hypertrophic scarring, possibly through an anti-inflammatory effect. Further exploration of this potential in additional clinical trials would be valuable.